Desigining an Integrated Product and Process Layout Using a Simulation: The Case of Plastic Bag Company - Naomi Melina Tanutomo; Tanti Octavia (International Journal of Industrial Research and Applied Engineering, 2016)
This paper proposed an integrated product and process layout for optimizing process plant layout using a simulation approach. The proposed layout was compared to the existing layout in terms of the average work-in-process and the average waiting time of work-in-process. Currently, the plastic bag company uses process layout for its production facility layout and the activity of material movement is conducted in a batch fashion. In the proposed layout, product layout was utilized for two of six processes and process layout was utilized for the rest. Product layout changed material movement from batch into one piece flow with material handling conveyor. Software ProModel 7.0 was run in 1 year run-time with 10 replications. The simulation results show that the proposed layout reduces the average work-in-process and work-in-process waiting time in warehouse inspection by 97.92% and 96.82%, respectively. The proposed layout eliminates 47.42 minutes of the average waiting time in welding cutting temporary storage area.